Identificación histológica del Helicobacter Sp. en la mucosa gástrica canina en Bucaramanga - Caceres Orduz, Eliana Maria; Joya Rodriguez, Yeison; Arcila Quiceno, Victor Hernan; Echeverri, Jorge (Spei Domus, 2007)
The gender of gastric Helicobacter. has been one of the most studied in the last time due to its implication in public health, after being discovered in 1979 by the pathologist Robin Warren, who associated it with the chronic gastritis. Research was carried out at the zoonoses center of the Health Secretary from Bucaramanga city together with the pathology department of the Industrial Santander University. The sample selected was 25 canines designated to Euthanasia regardless of: sex, physical condition. The samples were attained from the stomach, more specifically from the antrum and body. The macroscopic result was; 2 (8%) samples with gastric hypersecretion, 2 (8%) samples with gastric content, and 3 (12%) with thickening of the stomach pleats. The histological identification of the bacteria in a microscopic level, was made by means of a dyeing method using Hematoxiline and.Eosine whose result was: all samples positive to the presence of bacilar bacterias compatible with helicobacter sp. and evidence of injuries such as: vasodilatation in 88% of the samples, 4% polymorphonuclears , lymphocytes in 64% of the samples, the lymphoid accumulated in 16% samples, metaplasia in the gastric gland in 4% and macrophages in 28% of the samples with collagen increase in 32% of the samples. Then, ten samples were submitted to the hstopathological method of the Warthin-Starry dyeing and the result was all samples 100% positive to Helicobacter sp, It was established, that Helicobacter sp is a current inhabitant of the gastric canine flora and this bacteria doesn’t produce macroscopic damages in the canine gastric mucous membrane; at least in the canines that pass their lives in the public streets. These animals could be the principal reserve of this bacteria as a source of infection by either oral or fecal via that will serve for future research about transmissibility, having even an important effect in public health.